BIOELECTRICITY OF COCOA POD WASTE AS A SUBSTRATE IN A DOUBLE CHAMBER MICROBIAL FUEL CELL - Fitriana, Fitriana; Auliq, M Aan; Akbar, Faisal; Mubarok, Zidny (Jurnal Media Elektro, 2023)
Currently, the utilization of cocoa pod has not been maximized, resulting in waste and foul odors that disturb the environment. However, cocoa pod contain a relatively high amount of cellulose compounds that serve as an energy source or nutrition for bacteria to carry out metabolic activities, thus holding the potential to be used as a substrate in microbial fuel cells (MFC). Based on this, the aim of this research is to investigate the bioelectricity generated by a MFC using cocoa pod husk as a substrate, including voltage, current, and power density, in order to determine the potential of cocoa pod husk waste as an electrical energy source. In this study, a double chamber MFC consists of an anode chamber with copper electrodes and a cathode chamber with zinc electrodes, separated by a salt bridge. The bacteria used were Saccharomyces cerevisiae, and the substrate was made from cocoa pod husk waste. Bioelectricity testing involved measuring the voltage, current, and power density produced by the MFC over several minutes. The measurement results for maximum voltage, maximum current generated, and maximum electrical power (at 6 days) from the reactor were as follows: 36.0 mV, 0.19 mA, and 456 mW/m2, respectively.